Weight Loss Is Still an Essential Intervention in Obesity and its Complications: A Review - Jianzhong Xiao; Wenying Yang (Hindawi Limited, 2012)
The prevalence of obesity is more than 20% in many developed countries and it increases in developing countries. Obesity is associated with metabolic disorders, cardiovascular diseases, pulmonary diseases, digestive diseases, and cancers. Although other specific treatments for these complications exist, weight loss is still an essential intervention in obesity and its complications. Therapeutic life change, behavior modification, pharmacotherapy, and surgery are major approaches to weight loss. In addition, medicine used in diabetes such as Glucagon-like peptide-1 analogues may be a new type of medicine for obesity, at least for those obese patients with diabetes.